Intravenous Fosfomycin: A Potential Good Partner for Cefiderocol. Clinical Experience and Considerations - Andrea Marino; Stefano Stracquadanio; Edoardo Campanella; Antonio Munafò; Maria Gussio; Manuela Ceccarelli; Renato Bernardini; Giuseppe Nunnari; Bruno Cacopardo (MDPI AG, 2022)
Multidrug resistant Gram-negative bacteremia represents a therapeutic challenge clinicians have to deal with. This concern becomes more difficult when causing germs are represented by carbapenem resistant Acinetobacter baumannii or difficult-to-treat Pseudomonas aeruginosa. Few antibiotics are available against these cumbersome bacteria, although literature data are not conclusive, especially for Acinetobacter. Cefiderocol could represent a valid antibiotic choice, being a molecule with an innovative mechanism of action capable of overcoming common resistance pathways, whereas intravenous fosfomycin may be an appropriate partner either enhancing cefiderocol activity or avoiding resistance development. Here we report two patients with MDR Gram negative bacteremia who were successfully treated with a cefiderocol/fosfomycin combination.